Obesity and sexual behaviours - Zdrojewicz, Zygmunt; Seifert, Monika (Przewodnik Lekarza/Guide for GPs, 2011)
The obesity is serious health, economy and mental problem which is connected with adults but teenager and children as well. The cause of obesity’s is trying to find out in genetic base, in different life style and feeding – high caloric diet, easy availability of food with small physical activity. The obesity not only cradles bigger risk of diseases like diabetes type II, myocardial ischaemia and hypertension, change the hormone’s balance, but also has influence on the degradation of self-assessment and acceptation of restriction own body. The aim of this thesis is showing the relation between obesity and sexual behaviours.